2015
DOI: 10.1021/acs.macromol.5b00413
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Rearranged Poly(benzoxazole-co-imide) Membranes with Superior Mechanical Strength for Gas Separation Obtained by Tuning Chain Rigidity

Abstract: Thermally rearranged polybenzoxazoles (TR-PBO) are some of the most promising materials for gas separation because of their microporous and bimodal cavities that offer high gas transport performance. However, the brittleness of fully converted TR-PBO membranes has impeded their widespread industrial implementation. In this study, we prepared novel, thermally rearranged poly-(benzoxazole-co-imide) membranes (TR-PBOI) with improved mechanical strength and good gas separation performance. These membranes are base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…A similar trend was found in the comparison of the pristine polymer synthesized and characterized in the current study and the polymers reported earlier. The reported pristine 6FDA-HAB polymer thermally treated at 450°C ( 17 , 28 , 29 ) has lower permeability and selectivity than 6FDA-HAB-allyl thermally treated at 350°C. It should be emphasized that the gas transport properties of the CTR polymer treated at 350°C for the CO 2 /CH 4 gas pair are very close to the new 2008 Robeson’s upper bound and are better compared with the properties of the classical TR polymers thermally treated at 450°C.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar trend was found in the comparison of the pristine polymer synthesized and characterized in the current study and the polymers reported earlier. The reported pristine 6FDA-HAB polymer thermally treated at 450°C ( 17 , 28 , 29 ) has lower permeability and selectivity than 6FDA-HAB-allyl thermally treated at 350°C. It should be emphasized that the gas transport properties of the CTR polymer treated at 350°C for the CO 2 /CH 4 gas pair are very close to the new 2008 Robeson’s upper bound and are better compared with the properties of the classical TR polymers thermally treated at 450°C.…”
Section: Resultsmentioning
confidence: 97%
“… Samples are represented by symbols as follows: circles for 6FDA-HAB; squares for 6FDA-HAB-allyl; and diamonds ( 17 ), triangles pointing down ( 29 ), and triangles pointing up ( 28 ) for literature data on the polymer 6FDA-HAB synthesized under the same conditions. The largest symbols are for samples thermally treated at 350°C, and small symbols are for the samples thermally treated at 450°C.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, conventional polymeric membranes suffer from poor resistance to contaminants, low chemical and thermal stability, and a well‐known compromise between permeability and selectivity as shown in the upper bound Robeson curves . Intensive research efforts have been devoted to the rational design and preparation of novel nanoporous polymeric materials to overcome this limit, for example, by using thermally rearranged (TR) polymers and polymers of intrinsic microporosity (PIMs) . Guiver et al.…”
Section: Introductionmentioning
confidence: 99%
“…Colorful sphere: Data in this work (black for PIM‐1, blue for PIM‐1‐400, and red for PIM‐1‐450, with the thickness of 44 μm, 35 μm, and 33 μm, respectively). Open shapes: Data of TR‐PIM, UV rearranged PIM, thermal oxidative crosslinking PIM, thermal crosslinking PIM, photo oxide PIM, PIM‐based MMMs, and other polymeric TR membranes and CMS membranes, et al, from Reference 32, 34, 37, 38, 40, and 49–59 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%